2003
DOI: 10.1111/1467-9868.00382
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of General Non-Centred Orthant Probabilities

Abstract: The evaluation of the cumulative distribution function of a multivariate normal distribution is considered. The multivariate normal distribution can have any positive definite correlation matrix and any mean vector. The approach taken has two stages. In the first stage, it is shown how non-centred orthoscheme probabilities can be evaluated by using a recursive integration method. In the second stage, some ideas of Schläfli and Abrahamson are extended to show that any non-centred orthant probability can be expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
82
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(82 citation statements)
references
References 13 publications
(24 reference statements)
0
82
0
Order By: Relevance
“…As shown on p. 227 in Miwa et al (2003), the corresponding polyhedral cone Q can be represented as a set of points that can be expressed as a linear combination of edge vectorsṽ i of the cone Q with non-negative coefficients ξ i , z = ξ 1ṽ1 + · · · + ξ pṽ p , where the vectorsṽ i are the column vectors of the matrix V. Craig (2008) considered a procedure to evaluate orthant probabilities by splitting the cone Q into edge orthoscheme cones, where two edgesṽ i andṽ j of the cone are orthogonal if |i − j| > 1. He showed that the polyhedral cone Q can be split into a linear combination of edge orthoscheme cones.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…As shown on p. 227 in Miwa et al (2003), the corresponding polyhedral cone Q can be represented as a set of points that can be expressed as a linear combination of edge vectorsṽ i of the cone Q with non-negative coefficients ξ i , z = ξ 1ṽ1 + · · · + ξ pṽ p , where the vectorsṽ i are the column vectors of the matrix V. Craig (2008) considered a procedure to evaluate orthant probabilities by splitting the cone Q into edge orthoscheme cones, where two edgesṽ i andṽ j of the cone are orthogonal if |i − j| > 1. He showed that the polyhedral cone Q can be split into a linear combination of edge orthoscheme cones.…”
Section: Introductionmentioning
confidence: 89%
“…In this case, the polyhedral cone Q is represented by b j ( j−1) z j−1 + b j j z j ≥ 0. Miwa et al (2003) showed a method for evaluating this probability, which they called the orthoscheme probability, using recursive integration. They showed that non-centered orthant probability can be expressed as a linear combination of at most ( p − 1)!…”
Section: Introductionmentioning
confidence: 99%
“…Given the central role of the normal distribution, computation of multivariate normal probability functions has been extensively studied. For low dimensions, various deterministic numerical integration rules are available (Joe, 1995;Miwa et al, 2003). However, these rules are subject to the curse of dimensionality and cannot be employed for moderate to large dimensions, as those occurring in the type of animal behavior experiments that motivated this paper.…”
Section: Likelihood Inferencementioning
confidence: 99%
“…It employs a quasi-Monte Carlo algorithm, for which the computation time increases linearly with the dimension n and the computing time of ΔG(y) is proportional to n 2 (n ∈ N and n < 1000) (Genz and Bretz 1999). With a recursive linear integration procedure, mvtnorm calculates the MVN integral with even higher accuracy without compromising the computation time when n < 20 (Miwa et al 2003;Mi et al 2009).…”
Section: Introductionmentioning
confidence: 99%